Polyimide mixture and preparation method thereof

By using polyimide mixtures of modified inorganic fillers and crosslinking agents, the problem of existing polyimide insulating materials being prone to failure at high temperatures is solved, and the high-temperature insulation, wear resistance and impact resistance of the coating is achieved, and it is suitable for applications such as battery thermal runaway.

CN119592207APending Publication Date: 2025-03-11CHANGZHOU HUANFENG ELECTRICAL MATERIAL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411872536.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Existing polyimide insulating materials are prone to failure at high temperatures, the preparation process is complicated and the construction efficiency is low, making it difficult to meet the high-temperature insulation needs for applications such as battery thermal runaway.

Method used

Using a polyimide mixture, a coating with excellent insulating properties is prepared by adding binary anhydride, modified inorganic filler, crosslinking agent and other components, and using a coupling agent to modify the inorganic filler, adjust the weight ratio of the binary anhydride and the modified inorganic filler, add crosslinking agent and film forming additives, and prepare a coating with excellent insulating properties through specific process steps.

Benefits of technology

It improves the insulation pressure resistance, temperature resistance, wear resistance and impact resistance of the coating, avoids insulation failure caused by foaming on the surface of the coating, enhances adhesion with the metal substrate, and has good electrolyte resistance and acid and alkali resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005196102180000071
    Figure BDA0005196102180000071
Patent Text Reader

Abstract

The invention relates to the technical field of insulating materials, in particular to a polyimide mixture and a preparation method thereof. The preparation raw materials comprise binary anhydride, diisocyanate, a catalyst, a solvent, a modified inorganic filler, a cross-linking agent, a diluent and a coalescing agent. The modified inorganic filler is modified by using a coupling agent. The coating prepared from the polyimide mixture has good high temperature resistance and insulation performance, and also has good impact resistance, electrolyte resistance, acid and alkali resistance, friction resistance and good adhesive force with a metal substrate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of insulating materials, and specifically to a polyimide mixture and a preparation method thereof. Background Art

[0002] Battery thermal runaway refers to an accident in which an electrochemical cell raises its temperature through self-heating in an uncontrollable situation, usually caused by a periodic change in the internal heat of the battery. Thermal runaway is often accompanied by adverse conditions such as high temperature of deflagration, explosive shock, and electrolyte erosion. A common insulating protective layer is electrostatic powder spraying on metal parts. Electrostatic powder spraying has low cost and good insulation, but it is prone to failure at high temperatures. Polyimide is heat-resistant and has excellent mechanical properties. It is widely used in electronics and electrical engineering. However, its precursor needs to be cyclized at high temperature during the preparation process, and there are problems such as low solid content of high molecular weight solution, difficult solvent volatilization, multiple thermoforming, and low construction efficiency.

[0003] Chinese invention patent CN113223861B discloses a planar ultra-thin flexible high-voltage supercapacitor and its preparation method. Specifically, an ultra-thin flexible metal sheet is used as a conductive series medium, polytetrafluoroethylene is sprayed on the edges of adjacent metal sheets or coated with high-temperature resistant epoxy resin AB glue as an insulating layer, a polymer layer is obtained on the metal sheet by heat-curing polyimide precursor liquid or pasting PI film, and a graphene electrode material is prepared by laser processing the PI cured layer / film, a hydrogel electrolyte is dripped on its surface and copper foil is pasted as a current collector to complete the packaging of the supercapacitor. During the preparation process, its precursor needs to be cyclized at high temperature, and the process is relatively complicated. Summary of the invention

[0004] The first aspect of the present invention provides a polyimide mixture, the preparation raw materials including: dibasic anhydride, diisocyanate, catalyst, solvent, modified inorganic filler, crosslinking agent, diluent and film-forming aid; the modified inorganic filler includes modification using a coupling agent.

[0005] The dibasic anhydride includes at least one of metaphthalic anhydride (TMA), pyrophthalic anhydride (PMDA), ketone anhydride (BTDA), diphenyl ether dianhydride (ODPA), and biphenyl dianhydride (BPDA).

[0006] The diisocyanate includes at least one of toluene diisocyanate (TDI), isophorone diisocyanate (IPDI, diphenylmethane diisocyanate (MDI), dicyclohexylmethane diisocyanate (HMDI), hexamethylene diisocyanate (HDI), and lysine diisocyanate (LDI).

[0007] The solvent includes at least one of N-methylpyrrolidone, N,N-dimethylacetamide, N,N-dimethylformamide, dimethyl sulfoxide, sulfolane, and butyrolactone.

[0008] The catalyst includes at least one of triethylamine, triethylenediamine, ethyl tin octoate, dibutyltin dilaurate, iron octoate, cobalt octoate, tetraisobutyl titanate, potassium fluoride and potassium chloride.

[0009] The diluent includes at least one of N-methylpyrrolidone, N,N-dimethylacetamide, N,N-dimethylformamide, dimethyl sulfoxide, propylene carbonate, sulfolane, butyrolactone, toluene, xylene and cyclohexanone.

[0010] The film-forming aid includes at least one of a leveling agent, an anti-sagging agent and a defoaming agent.

[0011] Preferably, the leveling agent includes Guangzhou Core Chemical F100, the anti-sagging agent includes Guangzhou Core Chemical D640, and the defoaming agent includes BYK-333.

[0012] The weight ratio of the dibasic anhydride to the modified inorganic filler is 1:(0.5-1.5).

[0013] Preferably, the weight ratio of the dibasic anhydride to the modified inorganic filler is 1:(0.7-1.5).

[0014] This study found that the use of coupling agents to modify inorganic fillers can improve the insulation withstand voltage of the paint film prepared from the mixture. It is possible that the inorganic fillers are treated with coupling agents so that the filler gaps are infiltrated by the polymer solution, which improves the good dispersion with the polyimide solution, effectively avoids the agglomeration of the inorganic fillers, and avoids the insulation failure of the coating. Further research found that by limiting the weight ratio of dibasic anhydride and modified inorganic filler to 1: (0.5-1.5), the insulation failure caused by bubbling on the coating surface can be avoided. It is possible that the addition of a specific amount of inorganic filler helps the volatilization of the solvent in the mixture.

[0015] The added amount of the cross-linking agent is 2-8 wt % of the dibasic anhydride.

[0016] Preferably, the added amount of the cross-linking agent accounts for 3-7 wt % of the dibasic anhydride.

[0017] The coupling agent includes at least one of an aluminate coupling agent, a titanate coupling agent, and a silicate coupling agent.

[0018] Preferred are aluminate coupling agent (Nanjing Pinning DL-411), titanate coupling agent (Nanjing Tengchuan TC-130), and silicate coupling agent (Yangzhou Lida LD-792).

[0019] The coupling agent is added in an amount of 0.5-2.5 wt % of the inorganic filler.

[0020] Preferably, the coupling agent is added in an amount of 1-2 wt % of the inorganic filler.

[0021] The crosslinking agent includes an organic silicon epoxy crosslinking agent and / or a blocked polyisocyanate crosslinking agent.

[0022] Preferably, the model of the organosilicon epoxy crosslinking agent includes one of 9803-6 and 9803-5, and the model of the blocked polyisocyanate crosslinking agent includes HF-3180.

[0023] The inorganic filler includes at least one of boehmite, kaolin, talc and montmorillonite.

[0024] The particle size D95 of the inorganic filler is ≤10 microns.

[0025] The molar ratio of the dibasic anhydride to the diisocyanate is 1:(0.92-0.98).

[0026] Preferably, the added amount of the film-forming aid is 0.5-3 wt % of the polyimide mixture.

[0027] A second aspect of the present invention provides a method for preparing a polyimide mixture, comprising the following steps:

[0028] The solvent, dibasic anhydride and catalyst are mixed, a modified inorganic filler is added, and then a diisocyanate is added to react to obtain a mixture;

[0029] Adding a crosslinking agent, a diluent and a film-forming aid into the mixture, and grinding the mixture homogeneously to obtain a polyimide mixture;

[0030] The method of adding the modified inorganic filler includes adding the material in 2-5 batches.

[0031] Preferably, the method of adding the modified inorganic filler includes adding the material in 3-5 batches.

[0032] The reaction temperature is 80-120° C. and the reaction time is 3-6 hours.

[0033] The homogenization pressure is 20-30MPa, the mass is 40-50L / h, and the cooling water temperature is 10-20°C.

[0034] The viscosity of the mixture at 25° C. is 500-5000 cP.

[0035] Preferably, the viscosity of the mixture at 25° C. is 3000-5000 cP.

[0036] Beneficial Effects

[0037] 1. The use of coupling agents to modify inorganic fillers can improve the insulation withstand voltage of the coating prepared from the mixture.

[0038] 2. By limiting the weight ratio of dibasic anhydride to modified inorganic filler to 1: (0.5-1.5), insulation failure caused by blistering on the coating surface can be avoided.

[0039] 3. The amount of cross-linking agent added is 2-8wt% of the dibasic anhydride, which can simultaneously improve the heat resistance, wear resistance and impact resistance of the coating.

[0040] 4. The coating prepared from the mixture of the present application has excellent electrolyte resistance, acid and alkali resistance.

[0041] 5. The coating prepared from the mixture of the present application has good adhesion to the metal substrate. DETAILED DESCRIPTION

[0042] Example 1

[0043] A polyimide mixture is prepared from raw materials including: dibasic anhydride (phthalic anhydride, pyrophthalic anhydride), diisocyanate (diphenylmethane diisocyanate), catalyst (composite catalyst, triethylamine / ethyl tin octanoate), solvent (N-methylpyrrolidone), modified inorganic filler, crosslinking agent (organic silicon epoxy crosslinking agent), diluent (N, N-dimethylacetamide) and film-forming aid (BYK-333); the modified inorganic filler is modified by using a coupling agent (silicate coupling agent, Yangzhou Lida LD-792), and the specific steps are: taking 20kg of kaolin and adding it into a kneader, the rotation speed is 45rpm, adding 300g of LD-792 in three batches, kneading continuously for 45min, obtaining modified kaolin and setting aside.

[0044] A method for preparing a polyimide mixture comprises the following steps: adding phthalic anhydride (19.212 kg), phthalic anhydride monomer (2.942 kg), a composite catalyst triethylamine / ethyl tin octoate (55 g / 55 g) and N-methyl pyrrolidone (71.770 kg) respectively into a reaction kettle with double planetary stirring, stirring at 90°C for half an hour, adding diphenylmethane diisocyanate monomer (26.151 kg), with a large amount of gas escaping, adding modified kaolin 16.55 kg cumulatively in three batches, adding N-methyl pyrrolidone (20.74 kg), stirring for 1 hour, heating to 120°C, and continuing stirring for 4 hours. After the reaction was completed, the temperature was lowered to 35°C, and diluent N,N-dimethylacetamide (10Kg), 9803-5 silicone epoxy crosslinker (772g) and BYK-333 (300g) were added, and then further dispersed by grinding in a homogenizer equipped with 15°C cooling water to finally obtain a mixture with a solid content of 35wt% and a viscosity of 4300cP at 25°C.

[0045] Example 2

[0046] A polyimide mixture is prepared from raw materials including: dibasic anhydride (phthalic anhydride, ketone anhydride), diisocyanate (toluene diisocyanate), catalyst (composite catalyst, potassium fluoride / ethyl tin octoate), solvent (N-methylpyrrolidone), modified inorganic filler, crosslinking agent (organic silicon epoxy crosslinking agent), diluent (N, N-dimethylacetamide) and film-forming aid (BYK-333, D640); the modified inorganic filler is modified by using a coupling agent (titanate coupling agent, Nanjing Tengchuan TC-130), and the specific steps are: taking 40kg of boehmite and adding it into a kneader, the rotation speed is 45rpm, adding 600g of TC-130 type titanate coupling agent in three batches, kneading for 60min, obtaining modified boehmite for standby use.

[0047] A method for preparing a polyimide mixture comprises the following steps: adding phthalic anhydride (19.212 kg), ketoanhydride (3.222 kg), a composite catalyst potassium fluoride / ethyl tin octoate (60 / 75 g) and N-methylpyrrolidone (57.840 kg) respectively into a reaction kettle with double planetary stirring, stirring at 90°C for 1 hour, adding toluene diisocyanate (18.390 kg), with a large amount of gas escaping, adding modified boehmite (20.76 kg) cumulatively in three batches, and then adding N-methylpyrrolidone (28.55 kg), stirring for 1 hour, heating to 120°C, and continuing stirring for 4 hours. After the reaction was completed, the temperature was lowered to 35°C, and a diluent N,N-dimethylacetamide (10 Kg), a 9803-6 silicone epoxy crosslinker (778 g), BYK-333 (100 g) and a D640 anti-sagging agent (300 g) were added. The mixture was then further dispersed by grinding in a homogenizer equipped with 15°C cooling water to finally obtain a mixture with a solid content of 35 wt% and a viscosity of 3200 cP at 25°C.

[0048] Example 3

[0049] A polyimide mixture is prepared from raw materials including: dibasic anhydride (phthalic anhydride, biphenyl anhydride), diisocyanate (isophorone diisocyanate, diphenylmethane diisocyanate), catalyst (composite catalyst, triethylamine / potassium chloride), solvent (N,N-dimethylacetamide), modified inorganic filler, crosslinking agent (blocked polyisocyanate crosslinking agent), diluent (N,N-dimethylformamide) and film-forming aid (F100, BYK-333, D640); the modified inorganic filler is modified by using a coupling agent (aluminate coupling agent, Nanjing Pinning DL-411), and the specific steps are: taking 20kg of kaolin and adding it into a kneader, the rotation speed is 45rpm, adding 400g of DL-411 aluminate coupling agent in three batches, kneading continuously for 30min, obtaining modified kaolin and setting aside.

[0050] A method for preparing a polyimide mixture comprises the following steps: in a reaction kettle with double planetary stirring, respectively adding phthalic anhydride (19.212 kg), biphenyl dianhydride (2.942 kg), a composite catalyst triethylamine / potassium chloride (75 g / 80 g) and N, N-dimethylacetamide (89.56 kg), stirring at 90°C for 1 hour, adding isophorone diisocyanate (2.134 kg) and diphenylmethane diisocyanate (23.774 kg), with a large amount of gas escaping, adding modified kaolin (31.40 kg) cumulatively in three batches, and then adding N-methylpyrrolidone (53.27 kg), stirring for 1 hour, heating to 120°C, and continuing stirring for 4 hours. After the reaction was completed, the temperature was lowered to 35°C, and a diluent N,N-dimethylformamide (20 Kg), a HF-3180 blocked polyisocyanate crosslinker (1535 g), an F100 leveling agent (200 g), a D640 anti-sagging agent (400 g) and BYK-333 (200 g) were added, and then further dispersed by grinding in a homogenizer equipped with 15°C cooling water to finally obtain a mixture with a solid content of 30 wt% and a viscosity of 4200 cP at 25°C.

[0051] Comparative Example 1

[0052] The specific implementation is the same as Example 1; the difference is that the kaolin in Comparative Example 1 is not modified.

[0053] Comparative Example 2

[0054] The specific implementation is the same as Example 2; the difference is that the boehmite in Comparative Example 2 is not modified.

[0055] Comparative Example 3

[0056] The specific implementation method is the same as Example 1; the difference is that in Comparative Example 3, the amount of 9803-5 silicone epoxy crosslinking agent added is adjusted to 386g.

[0057] Comparative Example 4

[0058] The specific implementation method is the same as Example 2; the difference is that the amount of HF-3180 type blocked polyisocyanate cross-linking agent added in Comparative Example 4 is adjusted to 384g.

[0059] Comparative Example 5

[0060] The specific implementation is the same as Example 2; the difference is that the addition amount of modified boehmite in Comparative Example 5 is adjusted to 10.38 kg.

[0061] Comparative Example 6

[0062] The specific implementation method is the same as that of Example 3; the difference is that the addition amount of modified kaolin in Comparative Example 6 is adjusted to 38.37 kg.

[0063] Performance Testing Methods and Data

[0064] The mixtures prepared in the examples and comparative examples were cast onto 1.20×1.80m aluminum plates (treated with 300-mesh sandblasting, grinding, washing and drying) through a scraper with a 250-micron slit, and then baked at 80°C for two hours, 120°C for two hours, and 170°C for two hours, and then subjected to performance testing.

[0065] The membrane was subjected to performance tests, and the test data are listed in Table 1. “-” means no test was performed.

[0066] 1. Insulation withstand voltage: refer to GB / T1408.1, DC3000V, 60s, <3mA is qualified. Among them, Comparative Examples 1 and 2 have local tip discharge, which are unqualified; Comparative Example 5 is prone to produce pores and bubbles during coating baking, which is unqualified; Comparative Example 6 coating surface inorganic fillers are easy to aggregate, which is unqualified.

[0067] 2. Insulation resistance: Refer to GB / T10064, AC1000V, 60s, >1000MΩ is qualified.

[0068] 3. Acid resistance: Put the paint film sample into 0.1molL hydrochloric acid solution and soak it at 25℃ for 24h. The paint film is not damaged, DC3000V.60s, <3mA and AC1000v.60s, >1000MΩ, which is qualified.

[0069] 4. Alkali resistance: Put the paint film sample into 0.1molL sodium hydroxide dilution solution and soak it at 25℃ for 24h. The paint film is not damaged, DC3000V.60s, <3mA and AC1000v.60s, >1000MΩ, which is qualified.

[0070] 5. Electrolyte resistance: Put the paint film sample into the electrolyte (ethylene carbonate / dimethyl carbonate / diethyl carbonate=5 / 3 / 2w%) and place it in a 60℃ oven for 7 days. The paint film is not damaged, DC3000V.60s, <3mA and AC1000v.60s, >1000MΩ, which is qualified.

[0071] 6. High temperature insulation: 500±2℃ for 0.5h baking (oven). The paint film has no spontaneous combustion and no damage: DC500V, 60s, <3mA is qualified. Among them, the coating of comparative examples 3 and 4 is partially bulging and unqualified.

[0072] 7. Hundred grid test: refer to GB / T9826.

[0073] 8. Pencil hardness: refer to GB / T6739.

[0074] 9. Wear resistance: Taber abrasion tester, refer to GB-7012-T, load 1000g, rotation number 1000r, test mass loss.

[0075] 10. Impact resistance: GB / T1732-2020, impact mass: 1000g: impact head size: φ8mm: impact mode: positive impact (concave); impact height 100cm, the coating has no cracks or shedding, DC4500V.60s, <3mA, and AC1000V, 60s, >1000MΩ is qualified. Among them, the coating of comparative examples 3 and 4 has cracks and is unqualified.

[0076] The test instruments for test 1-6 are: electrical safety performance comprehensive analyzer (Qingdao Ainuo Intelligent Instrument Co., Ltd., AN9635HC).

[0077] Table 1

[0078]

[0079] The results in Table 1 show that the coatings prepared in Examples 1 to 3 have good high temperature resistance and insulation performance, as well as good impact resistance, electrolyte resistance, acid and alkali resistance, friction resistance and good adhesion to the metal substrate.

[0080] The tests of Example 1 and Comparative Example 1, as well as Example 2 and Comparative Example 2 show that the inorganic filler needs to be treated with a coupling agent to be well dispersed with the polyimide solution. Otherwise, the inorganic filler is prone to agglomeration and the filler gaps cannot be well infiltrated by the polymer solution, resulting in coating insulation failure.

[0081] The tests of Example 1 and Comparative Example 3, and Example 3 and Comparative Example 4 show that reducing the amount of cross-linking agent added does not affect the insulation performance of the coating at room temperature, but weakens the temperature resistance of the coating and also reduces the wear resistance and impact resistance of the coating.

[0082] The test results of Example 2 and Comparative Example 5 show that the addition of inorganic filler helps the volatilization of the solvent in the mixture. When too little inorganic filler is added, the solvent is difficult to volatilize, pores and bubbles are easily generated, and insulation failure occurs.

[0083] The test results of Example 1 and Comparative Example 6 show that even after the inorganic filler is treated with a coupling agent, the added amount cannot be too much, otherwise it will still lead to uneven dispersion of the polymer solution and the inorganic filler, aggregation of the inorganic filler, and insulation failure of the coating.

Claims

1. A polyimide mixture, characterized in that: The preparation raw materials include: dibasic anhydride, diisocyanate, catalyst, solvent, modified inorganic filler, crosslinking agent, diluent and film-forming aid; the modified inorganic filler includes modification by using coupling agent.

2. The polyimide mixture according to claim 1, characterized in that: The weight ratio of the dibasic anhydride to the modified inorganic filler is 1:(0.5-1.5).

3. The polyimide mixture according to claim 2, characterized in that: The added amount of the cross-linking agent is 2-8 wt % of the dibasic anhydride.

4. The polyimide mixture according to claim 1, characterized in that: The coupling agent includes at least one of an aluminate coupling agent, a titanate coupling agent, and a silicate coupling agent.

5. The polyimide mixture according to claim 4, characterized in that: The coupling agent is added in an amount of 0.5-2.5 wt % of the inorganic filler.

6. The polyimide mixture according to claim 1 or 3, characterized in that: The crosslinking agent includes an organic silicon epoxy crosslinking agent and / or a blocked polyisocyanate crosslinking agent.

7. The polyimide mixture according to claim 6, characterized in that: The inorganic filler includes at least one of boehmite, kaolin, talc and montmorillonite.

8. The polyimide mixture according to claim 7, characterized in that: The particle size D95 of the inorganic filler is ≤10 microns.

9. A method for preparing a polyimide mixture according to any one of claims 1 to 8, characterized in that: The following steps are involved: The solvent, dibasic anhydride and catalyst are mixed, a modified inorganic filler is added, and then a diisocyanate is added to react to obtain a mixture; A cross-linking agent, a diluent and a film-forming aid are added into the mixture, and the mixture is homogenized and ground to obtain a polyimide mixture.

10. The method for preparing the polyimide mixture according to claim 9, characterized in that: The method of adding the modified inorganic filler includes adding the material in 2-5 batches.

Citation Information

Patent Citations

  • A planar ultra-thin flexible high-voltage supercapacitor and a method for preparing the same

    CN113223861B

  • Multipurpose high-temperature-resistant inorganic nano hybrid polyimide resin coating adhesive and preparation method thereof

    CN116790184A

  • Wet-heat-resistant modified polyamide imide resin paste and electronic component using same

    JP1999012499A

  • Polyimide resin, method for producing the same, adhesive composition using the same, adhesive sheet, printing ink composition, and printed circuit board

    JP2010155975A